Supply of hospitals’ navigation system accessibility for various population groups from the perspective of lean production - A. A. Kurmangulov; S. D. Mazunina; Yu. S. Reshetnikova; N. S. Brynza (Исследования и практика в медицине)
The review is devoted to the analysis of the capabilities of modern navigation systems of healthcare facilities to supply an acceptable level of accessibility to the perception of navigation information for various categories of citizens. The hospitals’ navigation system is considered to be the most important part of the visualization system and one of the basic criteria for the quality of the space of health facilities when forming a new model of a medical organization providing primary health care in the framework of the federal project «Development of a primary health care system» of the national project «Healthcare». From the viewpoint of the management concept of lean production, the hospitals navigation system should be aimed at the complete elimination or reduction of unnecessary movements of visitors, as well as other types of basic and additional losses. The accumulated experience in implementing projects with the implementation of the concept of lean production in outpatient medical institutions of the Russian Federation suggests that a rationally designed and deployed navigation system can be an effective tool for visualization in a lean production methodology. Structural and technological solutions of an effective hospitals navigation system introducing the concept of lean production should take into account the possibility of perceiving navigation information by all population groups, including people with limited mobility: people with disabilities, people with disabilities, people with prams, etc. Technical means of informing, orienting and signaling for people with limited mobility is a complex of various technical means for providing visual, tactile, sound information, orientation in space. In addition, they indicate possible directions of movement and places of receipt of services that contribute to the accessibility, safety, information content and comfort of the healthcare facility. Modern hospitals must meet the requirements of ensuring accessibility and safety for people with disabilities and other people with limited mobility due to the implementation of a complex of architectural and planning, engineering, ergonomic, structural and organizational measures of the state program «Accessible Environment». The navigation system can be a key tool for these activities.